ANALISIS BUDAYA ORGANISASI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SUMEDANG - M. Tarom (Journal Of Regional Public Administration (JRPA), 2022)
The long-term goal of this research is the analysis of organizational behaviour in supporting the process of achieving the goals that have been set.  In particular, this research has a target to (1) analyze how the process of implementing organizational behaviour in improving performance, (2) analyzing the supporting factors of organizational behaviour and (3) analyzing the inhibiting factors in the implementation of organizational behaviour at the District Manpower and Transmigration Office Sumedang. The implementation of the research is designed to be carried out over a period of 1 month, with the stages of activities including identification and analysis of problems in the implementation of organizational culture in the Department of Manpower and Transmigration, Sumedang Regency, West Java Province.  This type of research is qualitative using a case study approach. Data collection techniques used by means of observation, interviews, documentation.  The data obtained were validated through: Persistence of observation, Triangulation of Data Sources, Adequacy of Reference.  The research data is processed through the following techniques: Data Reduction, Data Presentation, Conclusion Drawing, which aims to obtain data to support the final results of the study. The results showed that of the four dimensions of measuring the quality level of Organizational Culture, the Attention to Detail dimension is the dimension with the highest level of Organizational Culture quality compared to other dimensions.  While the People Orientation dimension has the lowest level of organizational culture quality, although the level is still quite adequate. The item “Employees are encouraged to work innovatively” is the item with the highest level of Organizational Culture quality compared to other items.  The item "One form of organizational attention to employees who excel is given social security" has the lowest level of organizational culture quality, although the level is still quite adequate.